THE INFLUENCE OF SALES GROWTH, ROA AND CURRENT RATIO ON STOCK PRICE IN PROPERTY COMPANIES AND REAL ESTATE - Cyndy Ariesty Manurung; Agatha Christine Parhusip; Lidia Mika Sintia S; Jholant Bringg Luck Amelia Br Sinaga; Taufik Akbar Parluhutan (Jurnal Ipteks Terapan, 2023)
This study aims to determine the effect of Sales Growth, Return on Assets (ROA), Current Ratio on Share Prices in Property and Real Estate companies on the Indonesia Stock Exchange for the period 2019 - 2021. This research is a quantitative type research, the sample used in this study was taken using purposive sampling method. Of the 65 Property and Real Estate companies in 2019-2021 that became the population in this study, 18 companies met the sampling criteria and the year of observation in this study was 3 (three) years and the data was obtained from www.idx.co.id . The type of data used in this study is secondary data, in the form of the company's annual financial statements, then the data is processed using multiple linear regression analysis using the SPSS application. The research results obtained indicate that Sales Growth, Return on Assets (ROA). Current Ratio has a significant effect on stock prices